STIGMA AND DISCRAMINATION AGAINT LGBTIQN+ WORKERS - Mahayot , Nattawirot; Chirinang, Pensri (Journal of MCU Nakhondhat, 2023)
The purpose of this academic article was to discuss stigma and discrimination against LGBTIQN+ workers which in the present, although it is open in terms of gender diversity but the issue of stigma and discrimination remains. As a worker with LGBTIQN+ in the government and private sectors, there are still many concerns that continue to be a problem for work to requires knowledge Competence comes in exchange for working stigmatized and discriminated against. In order not to cause problems and obstacles to work exclusion or discrimination of colleagues will not dare to show openly, gossip and contempt. Therefore, we must try to prove it with results. knowledge and abilities for accepting people of the opposite sex as laborers, revealing ongoing concern about dress codes, according to official regulations. Gender minority status was not seen as a professional hindrance for laborers in generally open-minded organization environments where exclusion and discrimination or disparaging gossip were rarely overt. Laborers were obliged to prove their own professional abilities to advance the acceptance of gender variant individuals as laborers. Thailand’s health education. Thailand’s health education model is still based on traditional models, without updates from current-day understanding of potential negative impact caused by interpersonal discrimination. One example is misrepresenting lesbian, gay, bisexual, transgender and intersex (LGBTIQN+) people as abnormal or mentally ill. This error might provoke rejection or hatred of minorities through unintentional promulgation of misleading opinions. As a result, some LGBTIQN+ remain closeted due to uncertainty about to remain safe in the workplace and in society.